Utilização de técnicas de geoprocessamento aplicado ao turismo rural - estudo de caso - Santiago/RS - Nunes, Giane Aparecida Polga (2004)
The tourism is one of the great activities that they collaborate with the world development, growing in a compared way the sections as informatization and telecommunications and it is one of the activities that more employments and profits generate in the world. Studies accomplished on the municipal district of Santiago and area, involving historical, cultural, educational, tourist and social aspects, they verified the possibility to create routes, trails and kindred stops that the characteristics and potentialities of the municipal district were disclosed and at the same time it rescued its history. Knowing that the rural tourism is an activity in growth in the whole world and source of generation of income, the City halls of the municipal districts of Santiago, São Miguel das Missões, Capão do Cipó e Bossoroca are developing the Project Tourist " Roads of Santiago from Brazil " and the present work seeks to develop a methodology using the geoprocessing techniques - SIG and GPS, applied to the rural tourism, to elaborate a rural tourist route prioritizing the historical colonization of the involved municipal districts as well as the valorization of the natural way, where he/she/it looks for to approach the tourist of the contact with the nature. The application of these geoprocessing techniques, Systems and Geographical Information and System of Global Positioning, as support tools in the elaboration of the tourist route demonstrated to be a necessary and effective tool, because it represents gain of time and economy for the implantation of the project. The pilgrim, making use of a GPS, it will travel the road, using the maps here developed and he will have in hands the whole necessary tool for its orientation. The application of these geoprocessing techniques is recommended in works that demand a speed and precision of data, facilitating the taking of decisions, as well as aiding in the implantation of new projects.